The Stress Management Teacher: Indonesia - syafaatul hidayati syafa (Program Studi Manajemen Pendidikan, 2020)
This article discusses teacher stress management which can be interpreted as the ability of a teacher to use available resources effectively to overcome various disorders and also mental and emotional disorders in him as a response or response. In this case there are three categories of potential sources of stress: environmental, organizational, and personal. the ability of each person to deal with stress varies from one to another. This is due to differences in perception, work experience, social support, and relevant personalities; Stress experienced by someone is characterized by symptoms, among others, as follows. Physiological, psychological, and behavioral symptoms. and efforts to overcome problems at work that can be a burden and even give them a sense of panic, which is to do things with relaxation and always think positively. The effort to overcome problems in work that can be a burden and even give a sense of panic to that is to do everything with relaxed and always think positive.